Diagnostic Accuracy of Transvaginal Ultrasound in Diagnosis of Endometrial Carcinoma among Women with Post-Menopausal Bleeding Taking Histopathology as Gold Standard - Khadija Tul Kubra, Fozia Hussain, Wajeeha Imran Andrabi, Faraz Bakht, Asia Raza, Samina (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Endometrial carcinoma is a significant cause of morbidity among post-menopausal women. Early detection through non-invasive methods like transvaginal ultrasound (TVUS) is essential, but its diagnostic accuracy varies compared to histopathology, the gold standard. Objective: To assess the diagnostic accuracy of transvaginal ultrasound (TVUS) in detecting endometrial carcinoma in postmenopausal women with bleeding, using histopathology as the gold standard. Study Design: cross-sectional study Study Setting: The study was carried out Gynaecology & Radiology Department of Lahore Medical and Dental College, Lahore from April 2023 to September 2023. Methodology: A total of 120 postmenopausal women with bleeding were enrolled. Each underwent transvaginal ultrasound (TVUS) to assess endometrial thickness, followed by an endometrial biopsy. An endometrial thickness threshold of 4 mm was used on TVUS. Histopathological findings were compared with TVUS results to determine sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV). Results: The mean endometrial thickness was 7.6 ± 3.2 mm. TVUS demonstrated a sensitivity of 83.3%, specificity of 33.3%, PPV of 29.4%, NPV of 85.7%, and an overall diagnostic accuracy of 45.8%. While effective in excluding malignancy, TVUS exhibited a high false-positive rate. Practical Implication: Transvaginal ultrasound can serve as a valuable non-invasive screening tool for early detection of endometrial carcinoma in women with postmenopausal bleeding, aiding in timely diagnosis and management. Conclusion: TVUS is a valuable screening tool with high sensitivity in detecting endometrial carcinoma. However, its low specificity highlights the need for histopathological confirmation to ensure accurate diagnosis. Keywords: Diagnostic accuracy, Endometrial carcinoma, Histopathology, Post-menopausal bleeding, Sensitivity, Specificity, Transvaginal ultrasound (TVUS).